Crisponi syndrome/cold-induced sweating syndrome type 2: Reprogramming of CS/CISS2 individual derived fibroblasts into three clones of one iPSC line - Buers, Insa; Schöning, Lara; Tomas Loges, Niki; Nitschke, Yvonne; Höben, Inga Marlena; Röpke, Albrecht; Crisponi, Laura; Omran, Heymut; Rutsch, Frank (Stem cell research, 2020)
Crisponi syndrome/cold-induced sweating syndrome type 2 (CS/CISS2) is a rare disease with severe dysfunctions of thermoregulatory processes. CS/CISS2 individuals suffer from recurrent episodes of hyperthermia in the neonatal period and paradoxical sweating at cold ambient temperatures in adolescence. Variants in CLCF1 (cardiotrophin-like-cytokine 1) cause CS/CISS2. Here, we summarize the generation of three clones of one stem cell line (iPSC) of a CS/CISS2 individual carrying the CLCF1 variant c.321C>G on both alleles. These patient derived iPSC clones show a normal karyotype, several pluripotency markers, and the ability to differentiate into the three germ layers.